Digital Interaction and Machine Intelligence Proceedings of MIDI'2022 - 10th Machine Intelligence and Digital Interaction - Conference, December 12-15, 2022, Warsaw, Poland (Online) - Biele, Cezary; Kacprzyk, Janusz; Kopeć, Wiesław; Owsiński, Jan W.; Romanowski, Andrzej; Sikorski, Marcin (Lecture Notes in Networks and Systems, 2023)
This open access book presents the proceedings of the 10th Machine Intelligence and Digital Interaction Conference. Artificial intelligence (AI) is rapidly affecting more aspects of our lives as a result of significant advancements in its research and the widespread usage of interactive technologies. This has led to the birth of several new social phenomena. Many nations have been working to comprehend these phenomena and discover solutions for moving artificial intelligence development in the proper direction to benefit individuals and communities at large. These efforts necessitate multidisciplinary approaches, encompassing not only the scientific fields involved in the creation of artificial intelligence and human-computer interaction but also strong collaboration between academics and practitioners. Because of this, the primary objective of the MIDI conference, which was conducted online on December 13-15, 2022, is to combine two up until recently distinct disciplines of research-artificial intelligence and human-technology interaction.